Comparative analysis of outsourcing and in house warehouse management system to improve productivity and stock accuracy - Untung Alamsah; Anang Muftiadi; â Ria Arifianti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study compares the impact of outsourced and in-house Warehouse Management Systems (WMS) on productivity and stock accuracy in the fast-moving consumer goods (FMCG) sector. Data was collected from a logistics services company in Palembang using quantitative methods, including measurements of productivity per person per hour and stock accuracy per SKU. Productivity was assessed based on items processed per unit time, while stock accuracy compared physical stock with system records. Additional data was gathered through a Google Form survey targeting operational staff and warehouse managers to understand the implementation of both WMS models. The survey covered critical processes such as putaway, picking, and inventory, providing insights into operational efficiency and challenges associated with each model. Dummy variable multiple regression was applied to evaluate the performance impact of each WMS model, supplemented by qualitative insights from structured interviews. Findings reveal that WMS in-house is better than outsourcing WMS. While 12.5% of respondents rated the outsourced WMS as inefficient, none reported inefficiencies in the in-house system. Additionally, 62.5% of respondents found the in-house WMS highly effective, citing smoother implementation and higher reliability. The in-house WMS also demonstrated superior operational efficiency, storage accuracy, and responsiveness. It provided better storage location guidance (33.3%) and faster, more accurate operator navigation (26.5%) compared to the outsourced system. Moreover, only 33.3% of respondents noted delays in resolving technical issues with the in-house system, versus 68.8% for the outsourced system. Statistical analysis further supported these findings, showing significant advantages for the in-house WMS in productivity (p=0.068) and stock accuracy (p=0.000). These results highlight the strategic advantages of adopting an in-house WMS, underscoring its role in enhancing operational efficiency and maintaining competitiveness in the dynamic FMCG market.